Hegel, In and Out of the Woods: Nature, Reflection, Capital. Issue 1 (April 2016) - Ellermann, Greg
Abstract : In the essays and lectures of his Jena period (1801–6), G. W. F. Hegel takes the measure of a nascent industrial capitalism, along with its consequences for life, consciousness, and labor. This article focuses on the philosopher's resistance to the exploitation of nature, essential to capitalist modernity and justified by a post-Enlightenment ethic of freedom. For Hegel, writing against the theorists of the autonomous, self-reflecting subject, nature is woven in with the spirit. So when he investigates the leap between the hand-tool and the machine, he is concerned not only with the machine's reshaping of consciousness. Just as disconcerting is the way machinery "deceives" nature, as it hastens on the "evaporation" of a bond between worker and world. If, under capitalism, all that is solid melts into air, for Hegel this change in the weather can be attributed to an industrial revolution in the mastery of nature.